2013
DOI: 10.1371/journal.pone.0054255
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Enhances the Antitumor Activity of Trichostatin A through Upregulation of p53 Protein Expression In Vitro and In Vivo

Abstract: This study investigated the effects of quercetin on the anti-tumor effect of trichostatin A (TSA), a novel anticancer drug, in vitro and in vivo and the possible mechanisms of these effects in human lung cancer cells. We first showed that quercetin (5 µM) significantly increased the growth arrest and apoptosis in A549 cells (expressing wild-type p53) induced by 25 ng/mL of (82.5 nM) TSA at 48 h by about 25% and 101%, respectively. However, such enhancing effects of quercetin (5 µM) were not significant in TSA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 39 publications
6
51
0
1
Order By: Relevance
“…This corroborates with findings from earlier studies which showed that treatment with combination of GO and AgNPs and combination of salinomycin 34,40,87 Combination of TSA and quercetin induced apoptosis through p53 activation in mouse tumors compared to control or cells treated with TSA alone. 88 The results from previous studies and the findings of the present study show that the combination of rGO-Ag and TSA induces cell death in a p53-dependent manner in human ovarian cancer cells.…”
Section: Rgo-ag and Tsa Cause Mitochondrial Dysfunctionsupporting
confidence: 73%
“…This corroborates with findings from earlier studies which showed that treatment with combination of GO and AgNPs and combination of salinomycin 34,40,87 Combination of TSA and quercetin induced apoptosis through p53 activation in mouse tumors compared to control or cells treated with TSA alone. 88 The results from previous studies and the findings of the present study show that the combination of rGO-Ag and TSA induces cell death in a p53-dependent manner in human ovarian cancer cells.…”
Section: Rgo-ag and Tsa Cause Mitochondrial Dysfunctionsupporting
confidence: 73%
“…As A549 line has been widely used as a model system to study human alveolar carcinoma, cytotoxic profile of flavonoids in these cells was previously characterized with the results very similar to those measured in our work. Indeed, the IC 50 value of 72.2 µM for quercetin is close to the inhibitory constants published by Loizzo et al (26), Tan et al (27)(28)(29), Robaszkiewicz et al (30), and Chan et al (31); and IC 50 values more than 100 µM were previously reported for fisetin (32), hesperetin (33-35), luteolin (32,36), chrysin (35), baicalein (34), daidzein (37), and genistein (38). Based on our results presented in this article, cytotoxic activity profiles of flavonoids were rather similar for both A549 and HCC-44 lung cancer lines, despite the gender difference of initial origin of these cells.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have reported that a combination of HDACIs, such as TSA combined with curcumin, produced significant antiproliferative and apoptotic effects compared with either agent alone. 40 The combination of quercetin and TSA significantly increased the cytotoxic effect in A549 cells, 41 whereas that of TSA and PdNPs produced a significant inhibitory effect on cell survival and HDAC activity in HeLa cells. In order to determine the correlation between cell viability and HDAC activity, we first evaluated the combinatorial effect of TUB-A and PdNPs on cell viability and HDAC activity in MDA-MB-231 human breast cancer cells.…”
Section: Results and Discussion Synthesis And Characterization Of Pdnpsmentioning
confidence: 99%